INSTRUCTIONAL FACILITIES AND THE ABILITIES OF NIGERIAN CERTIFICATE IN EDUCATION GRADUATES IN FEDERAL COLLEGE OF EDUCATION, YOLA - Ibrahim Gambo, Lawson Luka, Kwabe Tumba Madube, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This study was designed to assess the effects of instructional facilities on the abilities of Nigerian Certificate in Education Graduates in Federal College of Education, Yola. Two objectives were formulated to guide the conduct of the study. The study adopted the survey design. The population of the study comprises of all the graduates of the college from 2017 to 2022, lecturers and laboratory technicians of the departments in the various schools in the Federal College of Education, Yola. Due to the large number of lecturers in the individual departments of the various schools, and the laboratory technicians of the departments in the various schools in the Federal College of Education, Yola, the researchers selected a sample of 383 graduates, 69 lecturers and 23 laboratories technicians. The stratified, purposive and simple random sampling (SRS) techniques were adopted for the selection of the sampled population. The primary data was obtained for the study through the use of questionnaire designed by the researchers. The data collected for the study were analyzed using the simple percentage method of data analysis to analyze the respondent’s demographic data and ANOVA statistics to test the null and alternative hypotheses. The finding of the study revealed that instructional facilities have an influence on the academic performance of the NCE graduates. Based on the above conclusions the following were recommended; Communities need to embark on initiatives to tap funds to ensure that the school facilities are replenished and Government should provide facilities like modern laboratories, functional libraries, and comfortable classrooms for better academic performance;